Autorytet osoby i funkcji starszego cechu a obyczaj komunikatywny w instytucji cechowej w świetle protokołów piwowarów krakowskich (z lat 1729-1760) - Pałucka-Czerniak, Iwona (Acta Universitatis Lodziensis. Folia Linguistica, 2014)
This article presents the concept of authority exploited in historical studies of language. It shows a clash between the authority of the head of a corporation and the language custom of a speech community fixed in guild protocols. The influence of the older guild is reflected in the choice of the writer, in giving orders to write down contents of extreme relevance as well as in the theme of unusual records. The stylistic, linguistic and genre shape of records depend on the writer, who adapts it to the existing patterns of text. The relationship between the writer and the head of a guild sometimes manifests itself in the records of panegyric character. The situation changes when former writers become the head of guild, which will be discussed in the next publication.